Liquid component for electrolytic capacitor and electrolytic capacitor
The use of central atoms and ligands in the liquid component of electrolytic capacitors stabilizes the system, addressing heat and pH issues, resulting in improved thermal stability and reduced ESR.
Patent Information
- Application Number
- JP2021563970
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-09
- Filing Date
- 2020-12-08
- Publication Date
- 2025-01-31
- Estimated Expiration
- 2040-12-08
AI Technical Summary
Existing electrolytic capacitors face issues with increased ripple current leading to heat generation and performance degradation due to the thermal instability of salts like phthalic acid and borogy salicylic acid, and the pH increase causing conductive polymer deterioration.
A liquid component for electrolytic capacitors comprising central atoms such as boron, aluminum, or silicon, with ligands like oxygen or nitrogen, and a conductive polymer arranged between the anode and cathode, using complex anions to stabilize the system and maintain a pH below 6, enhancing thermal stability and conductivity.
The solution provides electrolytic capacitors with improved heat resistance and reduced ESR, maintaining performance under high temperatures by stabilizing the conductive polymer and preventing pH increase.
Smart Images

Figure 0007624609000008 
Figure 0007624609000009 
Figure 0007624609000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a liquid component for an electrolytic capacitor and an electrolytic capacitor including the same. [Background technology]
[0002] In an electrolytic capacitor having a liquid component such as an electrolyte, the liquid component can function as a de facto cathode material. Various studies have been conducted on the composition of the liquid component.
[0003] For example, Patent Document 1 describes the use of an electrolyte solution containing a salt of phthalic acid or borodisalicylic acid with an amine compound in an electrolytic capacitor. Patent Document 2 teaches an electrolytic capacitor containing a conductive polymer and a conductive auxiliary liquid. The conductive auxiliary liquid contains an organic solvent with a boiling point of 150° C. or higher and an aromatic compound having at least one hydroxyl group. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 11-67604 [Patent Document 2] International Publication No. 2013 / 94462 Brochure Summary of the Invention [Problem to be solved by the invention]
[0005] In recent years, there has been a demand for increasing the allowable ripple current of electrolytic capacitors. When the ripple current increases, the heat generated by the electrolytic capacitor increases, and the temperature of the electrolytic capacitor tends to rise. The salts of phthalic acid and borodisalicylic acid described in Patent Document 1 have low thermal stability, and therefore, when an electrolyte solution containing such salts is used, the performance of the electrolytic capacitor may decrease. In addition, the pH of the conductive auxiliary liquid described in Patent Document 2 tends to increase when the temperature of the electrolytic capacitor increases. When the pH increases, the conductive polymer deteriorates, and the performance of the electrolytic capacitor decreases. [Means for solving the problem]
[0006] In view of the above, one aspect of the present disclosure relates to a liquid component for an electrolytic capacitor, comprising: at least one central atom selected from the group consisting of boron, aluminum, and silicon; and a ligand having a plurality of coordinating atoms bonded to the central atom, wherein the coordinating atom is at least one selected from the group consisting of oxygen and nitrogen, and is bonded to a carbon atom that does not have an oxo group.
[0007] Another aspect of the present disclosure relates to an electrolytic capacitor including an anode body having a dielectric layer formed on a surface thereof, a cathode body, and a conductive polymer and the above-described liquid component disposed between the anode body and the cathode body.
[0008] Yet another aspect of the present disclosure relates to an electrolytic capacitor including an anode body having a dielectric layer formed on a surface thereof, a cathode body, and the above-described liquid component disposed between the anode body and the cathode body. Effect of the Invention
[0009] According to the above aspects of the present disclosure, it is possible to provide an electrolytic capacitor and a liquid component for an electrolytic capacitor having excellent heat resistance. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a schematic cross-sectional view of an electrolytic capacitor according to an embodiment of the present disclosure. [Diagram 2]2 is a schematic diagram for explaining the configuration of a capacitor element according to the same embodiment. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The novel features of the present invention are set forth in the appended claims, but the present invention, both in terms of structure and content, together with other objects and features of the present invention, will be better understood from the following detailed description taken in conjunction with the drawings.
[0012] The electrolytic capacitor according to the present disclosure includes an anode body having a dielectric layer formed on a surface thereof, a cathode body, and a liquid component disposed between the anode body and the cathode body.
[0013] The liquid component includes at least one central atom selected from the group consisting of boron, aluminum, and silicon, and a ligand having a plurality of coordinating atoms bonded to the central atom, in other words, the ligand has a plurality of coordinating atoms bonded to the central atom.
[0014] The coordinating atom is at least one selected from the group consisting of an oxygen atom and a nitrogen atom, and is bonded to a carbon atom that does not have an oxo group (=O). When the coordinating atom is an oxygen atom, the oxygen atom is an oxygen atom that does not form a carboxy group or a carboxy anion.
[0015] More specifically, the oxygen atom that is the coordinating atom may be an alcoholic or phenolic hydroxyl group or alkoxy oxygen, or an oxy group. Among these, it is preferable that an alcoholic or phenolic alkoxy oxygen is bonded to the central atom because the bond with the central atom is stable.
[0016] On the other hand, when the coordinating atom is a nitrogen atom, the nitrogen atom is a nitrogen atom that forms an amino group, an amide group, an imide group, an imide anion, or the like.
[0017] A coordination compound is composed of a central metal and a ligand. The coordination compound includes a complex and a complex salt. The ligand is not particularly limited, but may form a complex anion together with the central atom. In other words, the coordination compound may be a complex anion. A coordination compound (first coordination compound) is formed by coordinating an organic molecule having a plurality of coordination atoms (in other words, a coordinating organic compound) to a central metal. In other words, the first coordination compound has a ligand derived from such an organic molecule (coordinating organic compound). The ligand may have a structure in which a hydrogen atom, a hydroxyl group, an amino group, or an imino group bonded to the coordination atom is detached from the organic molecule.
[0018] The ligand preferably contains a substituent having electron-withdrawing properties. Such a substituent is likely to stabilize the electrons of the ligand's coordinating atom, so that the product of hydrolysis is unlikely to corrode the electrodes of the capacitor. Here, examples of the electron-withdrawing substituent include a nitro group, a carboxy group, an ester group, a halogen atom (such as a fluorine atom or a chlorine atom), an acyl group, a tosyl group, a keto group, a cyano group, and a methylsulfonyl group.
[0019] On the other hand, the ligand may contain a substituent having electron-donating properties. Such a substituent contributes to the stability of the liquid component, particularly when water is added or in a high-humidity environment, since electrons flow into the vacant orbital on the central atom and the component is easily stabilized. Here, examples of the electron-donating substituent include an amino group, an alkyl group, an aryl group (such as a phenyl group), and an alkoxy group.
[0020] The ligand may be derived from, for example, a polyol having an aromatic ring and a group containing at least a first hydroxyl group and a second hydroxyl group. That is, the organic molecule (coordinating organic compound) may be a polyol. The ligand derived from a polyol means a residue obtained by removing a hydrogen atom and / or a hydroxyl group from the polyol, and / or the polyol. The first hydroxyl group may be bonded to the aromatic ring. The group containing a second hydroxyl group may be bonded to the ortho position relative to the first hydroxyl group of the aromatic ring. The group containing a second hydroxyl group may be a second hydroxyl group or an alkyl group having a second hydroxyl group. Examples of the alkyl group having a second hydroxyl group include alkyl groups having 1 to 4 carbon atoms. Examples of the alkyl group having a second hydroxyl group include a methylol group, an ethylol group, a propylol group, or a butyrol group. A methylol group is preferable from the viewpoint of stability of the complex anion.
[0021] More preferably, the organic molecule may be a compound represented by the following general formula (1), (2), (3), (4), (5) or (6). [ka] [ka] [R 1 , R 2 , R 3 , R 4 , R 5 and R 6 each independently represents a hydrogen atom, a halogen atom, a hydroxy group, an alkoxy group having 1 to 10 carbon atoms, a carboxy group, a group having 2 to 10 carbon atoms and an ester bond, a saturated aliphatic hydrocarbon group having 1 to 24 carbon atoms which may have a substituent, an unsaturated aliphatic hydrocarbon group having 2 to 24 carbon atoms which may have a substituent, or an aromatic hydrocarbon group having 6 to 14 carbon atoms which may have a substituent.]
[0022] Examples of the halogen atom include a fluorine atom, a chlorine atom, and a bromine atom.
[0023] Examples of the alkoxy group having 1 to 10 carbon atoms include a methoxy group, an ethoxy group, an n- or iso-propoxy group, an n-, sec-, iso- or tert-butoxy group, an n-pentoxy group, an n-hexoxy group, an octoxy group, a decoxy group, and a phenoxy group.
[0024] Examples of the group having an ester bond and having 2 to 10 carbon atoms include an alkoxycarbonyl group having a carbon number of 2 to 10. Examples of the alkoxycarbonyl group include a group in which a hydrogen atom of a carboxy group is substituted with a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a pentyl group, an octyl group, or a nonyl group.
[0025] Examples of the saturated aliphatic hydrocarbon group having 1 to 24 carbon atoms which may have a substituent include an alkyl group having 1 to 24 carbon atoms and a cycloalkyl group having 3 to 24 carbon atoms. Examples of the alkyl group include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, a 2-methylbutyl group, a 3-methylbutyl group, a 2-ethylpropyl group, an n-hexyl group, a 1-methylpentyl group, a 2-methylpentyl group, a 3-methylpentyl group, a 4-methylpentyl group, a 1-ethylbutyl group, a 2-ethylbutyl group, a 1-propylpropyl group, a 2-propylpropyl group, a 1-isopropylpropyl group, a 2-isopropylpropyl group, an n-heptyl group, a 1-methylhexyl group, a 2-methylhexyl group, a 3-methylhexyl group, a 4-methylhexyl group, a 5-methylhexyl group, a 1-ethylpentyl group, a 2-ethylpentyl group, a 3-ethylpentyl group, a 2,2-dimethylpropyl group, and a 1-propylbutyl group. , 2-propylbutyl group, 1-iso-propylbutyl group, 2-iso-propylbutyl group, n-octyl group, 1-methylheptyl group, 2-methylheptyl group, 3-methylheptyl group, 4-methylheptyl group, 5-methylheptyl group, 6-methylheptyl group, 1-ethylhexyl group, 2-ethylhexyl group, 3-ethylhexyl group, 4-ethylhexyl group, 1-propylpentyl group, 2-propylpentyl group, 1-iso-propylpentyl group, 2-iso-propylpentyl group, 3-propylpentyl group, 3-iso-propylpentyl group, 1-butylbutyl group, 2-butylbutyl group, 1-iso-butylbutyl group, 2-iso-butylbutyl group, 1-tert-butylbutyl group, 2-tert-butylbutyl group, 1,1,3,3-tetramethylbutyl group, nonyl group and decyl group. The number of carbon atoms in the alkyl group may be 1 to 20, 1 to 16, or 1 to 12, etc. Examples of the cycloalkyl group include a cyclopentyl group, a cyclohexyl group, a cyclopentyl group, and a cyclooctyl group, etc. The number of carbon atoms in the cycloalkyl group may be 5 to 10, or 5 to 8.
[0026] Examples of the unsaturated aliphatic hydrocarbon group having 2 to 24 carbon atoms, which may have a substituent, include an alkenyl group. Examples of the alkenyl group include a vinyl group, a propenyl group, a butenyl group, a pentenyl group, a hexenyl group, an octenyl group, a decenyl group, and an isopropenyl group. The number of carbon atoms in the unsaturated aliphatic hydrocarbon group may be 2 to 18.
[0027] Examples of the substituent that the saturated aliphatic hydrocarbon group having 1 to 24 carbon atoms or the unsaturated aliphatic hydrocarbon group having 2 to 24 carbon atoms may have include a hydroxy group, an alkoxy group (e.g., an alkoxy group having 1 to 4 carbon atoms), a carboxy group, a nitro group, a halogen atom, a cyano group, and an amino group.
[0028] Examples of the aromatic hydrocarbon group having 6 to 14 carbon atoms, which may have a substituent, include an aryl group and an arylalkyl group (or an aralkyl group). Examples of the aryl group include a phenyl group, a tolyl group, a xylyl group, and a naphthyl group. The aryl group may have an aromatic hydrocarbon ring having 6 to 10 carbon atoms. Examples of the arylalkyl group include an alkyl group having 1 to 4 carbon atoms and an aryl group having 6 to 10 carbon atoms. Examples of the arylalkyl group include a benzyl group and a phenethyl group. Examples of the substituent include an alkyl group (such as an alkyl group having 1 to 6 carbon atoms), a hydroxy group, an alkoxy group (such as an alkoxy group having 1 to 4 carbon atoms), a carboxy group, a nitro group, a halogen atom, a cyano group, and an amino group.
[0029] More specifically, examples of polyols having a secondary hydroxy group bonded to an aromatic ring include catechol, pyrogallol, gallic acid, gallic acid esters (such as alkyl gallates (esters with alkyls having 1 to 4 carbon atoms)), hexahydroxybenzene, 1,2-dihydroxynaphthalene, 2,3-dihydroxynaphthalene, 4,4'-(2,3-dimethyltetramethylene)dipyrocatechol, 2,3,4,4'-tetrahydroxydiphenylmethane, etc. The aromatic rings of these polyols may have a substituent bonded thereto.
[0030] Typical examples of polyols having an alkyl group (such as a methylol group) having a primary hydroxyl group and a secondary hydroxyl group include salicyl alcohol, 2,5-dihydroxybenzyl alcohol, 2,6-bis(hydroxymethyl)-p-cresol, etc. The aromatic ring of these polyols may have a substituent bonded thereto.
[0031] Examples of the substituent that the aromatic ring of the polyol may have include R 1 ~R 6 The groups or atoms described for (excluding hydrogen atoms) are included.
[0032] The number of polyol molecules coordinated to one central atom may be one molecule or two or more molecules. From the viewpoint of the stability of the complex anion, a polyol may be selected in which two or more molecules (for example, two or three molecules) of polyol are coordinated to two central atoms. The number of molecules corresponds to the number of ligands coordinated to one central atom.
[0033] When the central atom is boron or aluminum, for example, a tetracoordinated complex anion can be formed.Typical examples include complex anions in which two molecules of diol are dehydrated and coordinated to a boron atom or an aluminum atom (typically, borodicatechol, etc.).When the central atom is silicon, for example, a pentacoordinated or hexacoordinated complex anion can be formed.Typical examples include complex anions in which three molecules of diol are dehydrated and coordinated to a silicon atom.
[0034] From the viewpoint of reducing the ESR of the electrolytic capacitor, it is preferable that the electrolytic capacitor further has a conductive polymer disposed between the anode body and the cathode body. The conductive polymer is, for example, a π-conjugated conductive polymer, and is usually doped with a dopant to improve the conductivity. It is considered that the liquid component contains a first coordination compound (complex anion, etc.), which suppresses de-doping of the dopant, thereby suppressing deterioration of the conductive polymer or a decrease in the conductivity.
[0035] The pH of the liquid component is preferably 6 or less, more preferably 4 or less, and even more preferably 3.8 or less or 3.6 or less. By setting the pH of the liquid component to 4 or less, deterioration of the conductive polymer is more significantly suppressed.
[0036] The first coordination compound (complex anion, etc.) exhibits acidity and can contribute to controlling the pH within the above range. However, the liquid component may further contain an acid component.
[0037] The concentration of the complex anion contained in the liquid component may be, for example, more than 0.1% by mass, or may be 1.0% by mass or more. By containing the complex anion in this way, the stability of the liquid component at high temperatures is greatly improved, and the heat resistance of the electrolytic capacitor is also significantly improved. However, from the viewpoint of maintaining a suitable viscosity of the liquid component, the content of the complex anion contained in the liquid component may be, for example, 30% by mass or less, or 20% by mass or less.
[0038] Here, the concentration of complex anion is defined as the maximum amount of complex anion that can be formed by the central atom contained in the liquid component and the ligand having a plurality of coordination atoms having the above structure. Here, regardless of whether or not a complex anion is actually formed, the maximum amount is calculated on the assumption that the central atom and the ligand all form complex ions. However, when the equivalent of the central atom and the equivalent of the ligand are different, the above maximum amount can be calculated from the equivalent of the smaller one.
[0039] The quantitative and qualitative analysis of the complex anion can be carried out, for example, by the following method.
[0040] <Qualitative analysis> First, 30 mL of the liquid component is weighed into a glass container with a sealed lid, and the infrared absorption spectrum (IR) of the liquid component in the container is measured using a specified measuring device (IRSprit [Shimadzu Corporation]). Next, the container containing the liquid component is sealed and kept in a high-temperature environment for a certain period of time. The liquid component in the container is then allowed to cool, and the IR is measured again. The stability of the complex anion can be evaluated from the change in the stretching vibration spectrum of the bond between the central atom and the coordinating atoms. It can be said that the smaller the spectral change, the higher the stability of the complex anion.
[0041] <Quantitative analysis> First, 30 mL of the liquid component is weighed into a glass container with a sealed lid, and the nuclear magnetic resonance spectrum (NMR) of the liquid component in the container is measured using a specified measuring device (AVANCE III HD [BRUKER]), and the initial complex anion generation ratio (G0) is calculated from the peak intensity. Next, the container containing the liquid component is sealed and kept in a high-temperature environment for a certain period of time. After that, the liquid component in the container is allowed to cool, and NMR is measured again to determine the generation ratio (G1) of the complex anion and unreacted organic molecules. The decomposition rate of the complex anion is calculated using the following formula, and the stability of the complex anion can be evaluated. It can be said that the smaller the decomposition rate, the higher the stability of the complex anion.
[0042] Complex anion generation ratio G1 (%) = (complex anion peak intensity) / (complex anion peak intensity + unreacted organic molecule peak intensity) × 100 Decomposition rate of complex anion (%) = Initial complex anion generation ratio G0 (%) - Complex anion generation ratio G1 (%)
[0043] The liquid component may further include at least one selected from the group consisting of cations containing nitrogen atoms and cations containing phosphorus atoms. These cations are considered to play a role in, for example, increasing the stability of the complex anion, increasing the degree of dissociation of the acid component, and increasing the electrical conductivity of the liquid component. The cations containing nitrogen atoms may be ammonium ions of various structures, and the cations containing phosphorus atoms may be phosphonium ions. That is, at least one selected from the group consisting of cations containing nitrogen atoms and cations containing phosphorus atoms may be an onium cation. The content of the onium cations contained in the liquid component may be, for example, 0.1% by mass or more, and may be 30% by mass or less.
[0044] The nitrogen atom-containing cation may be at least one selected from the group consisting of secondary ammonium ions, tertiary ammonium ions, and quaternary ammonium ions. The amine that generates the ammonium ion may be an aliphatic amine, an aromatic amine, or a heterocyclic amine. Among them, an aliphatic amine having a molecular weight of 72 to 102 is preferred because of its high degree of dissociation.
[0045] Examples of amines that generate ammonium ions include methylamine, dimethylamine, trimethylamine, ethylamine, diethylamine, triethylamine, ethylenediamine, N,N-diisopropylethylamine, tetramethylethylenediamine, hexamethylenediamine, spermidine, spermine, amantadine, aniline, phenethylamine, toluidine, pyrrolidine, piperidine, piperazine, morpholine, imidazole, pyridine, pyridazine, pyrimidine, pyrazine, 4-dimethylaminopyridine, etc. These may be used alone or in combination of two or more.
[0046] The quaternary ammonium ion may be an ion of an amidine. Examples of amidines that generate ammonium ions include acetamidine, 1-amidinopyrazole, benzamidine, and pyridine-3-carboximidamide. The amidine may have a substituent (such as the electron-withdrawing or electron-donating substituents exemplified above).
[0047] The ions of amidine also include imidazolium (i.e., imidazolium ions). The imidazolium may be a cation having a 1,3-diazole ring. The imidazolium may have a substituent (such as the electron-withdrawing or electron-donating substituents exemplified above). The imidazolium may include imidazolium and imidazolium having a substituent (such as an alkyl group or an aryl group) at least one of the 1st and 3rd positions. Examples of imidazolium having a substituent at least at the 1-position or the 3-position include 1,3-dimethylimidazolium, 1,3-diisopropylimidazolium, 1,3-dibutylimidazolium, 1,2,3,4-tetramethylimidazolium, 1-methyl-3-propylimidazolium, 1-ethyl-3-methylimidazolium, 1-ethyl-2,3-dimethylimidazolium, 1-butyl-3-methylimidazolium, and 1-benzyl-3-methylimidazolium.
[0048] In electrolytic capacitors that do not contain conductive polymers (for example, aluminum electrolytic capacitors), it is preferable to include amidine ions in the liquid component in order to suppress an increase in ESR.
[0049] When the liquid component is kept at a temperature of 145°C for 1000 hours, the increase in pH can be suppressed to 3 or less. In other words, when the pH of the liquid component before being kept at a temperature of 145°C for 1000 hours is X, and the pH after being kept at a temperature of 145°C for 1000 hours is Y, the difference between Y and X (YX) can be suppressed to 3 or less. This means that the liquid component is highly stable and the pH is unlikely to increase even at high temperatures (i.e., it is unlikely to change from acidic to alkaline). It is considered that the above ligand is unlikely to decompose and is unlikely to increase acid components such as carboxylic acids. Therefore, corrosion of the electrodes of the electrolytic capacitor is unlikely to occur. It is also considered that the above ligand has the effect of stabilizing carboxylic acids coexisting in the liquid component.
[0050] Specifically, the change in pH can be measured by the following method. First, 30 mL of the liquid component is weighed into a glass container with a sealed lid, and the pH (X) of the liquid component in the container at 25°C is measured using a specified measuring device (HM-41X manufactured by DKK-TOA). Next, the container containing the liquid component is sealed and kept in an oven at 145°C for 1000 hours. After that, the temperature of the liquid component in the container is returned to 25°C, and the pH (Y) is measured again. The change in pH can be evaluated by calculating the difference between the measured values Y and X.
[0051] In order to suppress the change in pH (YX) to 3 or less, it is sufficient to include an appropriate amount of a first coordination compound (complex anion, etc.) in the liquid component. In addition, when an acid component is included in the liquid component, it is preferable to suppress the amount of carboxylic acid used. At high temperatures, carboxylic acid is likely to undergo a side reaction (e.g., esterification reaction) with the solvent contained in the liquid component or moisture entering from the outside. When the acid component decreases due to the side reaction, the pH tends to increase. For the above reasons, the content of carboxylic acid in the liquid component is desirably, for example, 5% by mass or less, and more preferably 1% by mass or less.
[0052] Among carboxylic acids, aromatic carboxylic acids are relatively stable. Among them, aromatic carboxylic acids having at least two carboxy groups and at least one aromatic ring are relatively stable against esterification reactions. From the viewpoint of suppressing the increase in viscosity of the liquid component, it is desirable for the aromatic carboxylic acid to have one or two aromatic rings (such as a C6 benzene ring and / or a C10 naphthalene ring).
[0053] As the aromatic carboxylic acid, a more stable divalent to tetravalent carboxylic acid is preferred, and it is desirable that two or more carboxy groups are directly bonded to the ortho positions of the aromatic ring. Specifically, phthalic acid, pyromellitic acid, etc. can be used as the aromatic carboxylic acid. Among them, phthalic acid is preferred, and o-phthalic acid is particularly preferred.
[0054] A second coordination compound (or condensate (complex anion, etc.)) of a carboxylic acid and an inorganic acid (e.g., boric acid, phosphoric acid, etc.) may be used. As the second coordination compound, for example, a coordination compound of a carboxylic acid and boric acid is preferable. Specific examples of the second coordination compound that can be used include borodisalicylic acid, borodiglycolic acid, and borodisalic acid. Such second coordination compounds have higher thermal stability than carboxylic acids, but are easily decomposed at high temperatures, for example, 150°C or higher.
[0055] The amount of complex anion and cation (electrolyte salt) contained in the liquid component is preferably 0.1% by mass or more and 50% by mass or less, and the stability of the liquid component at high temperatures is greatly improved, and the heat resistance of the electrolytic capacitor is also significantly improved. However, from the viewpoint of maintaining a suitable viscosity of the liquid component, the content of the electrolyte salt contained in the liquid component may be, for example, more than 1% by mass and less than 30% by mass, or more than 10% by mass and less than 25% by mass.
[0056] The molar ratio of the complex anion to the cation (=complex anion / cation) is, for example, from 0.5 to 2 or from 0.8 to 1.2, and preferably from 0.9 to 1.1. In this case, the stability of the liquid component at high temperatures is further increased, and the stability of the complex anion and the degree of dissociation of the acid component are further increased, thereby enabling the electrical conductivity of the liquid component to be further increased.
[0057] The ratio of the complex anion in the electrolyte salt is preferably 15% by mass or more or 30% by mass or more, more preferably 50% by mass or more or 60% by mass or more. In this case, the stability of the liquid component at high temperatures can be further improved. The ratio of the complex anion in the electrolyte salt is 90% by mass or less, preferably 85% by mass or less or 80% by mass or less, and more preferably 75% by mass or less or 70% by mass or less. In this case, the stability of the complex anion and the degree of dissociation of the acid component are further improved, and the conductivity of the liquid component can be further improved. These lower and upper limits can be combined arbitrarily.
[0058] The amount of water contained in the liquid component may be 0.1% by mass or more and 30% by mass or less, or 0.5% by mass or more and 30% by mass or less. In this way, even if a relatively large amount of water is contained, the first coordination compound (complex anion, etc.) is not easily hydrolyzed, so the pH of the liquid component can be stably maintained. In addition, acid components such as carboxylic acids are not easily increased, and corrosion of the electrodes of the electrolytic capacitor is not easily caused.
[0059] The liquid component may further include a solvent. The type of the solvent is not particularly limited, but it is desirable to use at least a polymer polyether solvent in terms of improving the heat resistance of the electrolytic capacitor. Here, the weight average molecular weight (Mw) of the polymer polyether solvent is, for example, 150 or more. The polymer polyether solvent has high thermal stability and is unlikely to cause a side reaction with the ligand. Examples of the polymer polyether solvent include polyalkylene glycols such as polyethylene glycol and polypropylene glycol, polyglycerin, and polyethers (for example, ethers obtained by alkylating the terminals of polyalkylene glycol or polyglycerin). Since it is desirable for the polymer polyether solvent to have as low a viscosity as possible, it is desirable for it not to contain an aromatic ring having a rigid structure. The weight average molecular weight (Mw) of the polyethylene glycol may be, for example, 190 to 400, or 200 to 300.
[0060] In this specification, the weight average molecular weight (Mw) is a value calculated as polystyrene measured by gel permeation chromatography (GPC). GPC is usually measured using a polystyrene gel column and water / methanol (volume ratio 8 / 2) as the mobile phase.
[0061] The content of the polymeric polyether solvent in the liquid component may be, for example, 0.5% by mass or more, 1% by mass or more, and preferably 20% by mass or more. The content of the polymeric polyether solvent may be 90% by mass or less.
[0062] Solvents other than the polymer polyether solvent may include low molecular weight glycol compounds such as ethylene glycol, diethylene glycol, triethylene glycol, and propylene glycol, and glycerin. It is believed that low molecular weight glycol compounds or glycerin can increase the orientation of the conductive polymer, improve the conductivity, and reduce the ESR. Among them, ethylene glycol is preferable because it has a relatively low viscosity, high thermal conductivity, and excellent heat dissipation.
[0063] The content of ethylene glycol in the liquid component may be, for example, 3.0% by mass or more, preferably 10% by mass or more, and may be 90% by mass or less.
[0064] The liquid component may further contain, for example, a sulfone compound, a lactone compound, a carbonate compound, etc. as a solvent. As the sulfone compound, sulfolane, dimethyl sulfoxide, diethyl sulfoxide, etc. may be used. As the lactone compound, γ-butyrolactone, γ-valerolactone, etc. may be used. As the carbonate compound, dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (PC), fluoroethylene carbonate (FEC), etc. may be used. As the solvent, one type may be used alone, or two or more types may be used in combination. From the viewpoint of the synthesis of complex anions, it is preferable to use a lactone compound.
[0065] The conductive polymer disposed between the anode body and the cathode body may be synthesized by applying a solution containing a monomer, a dopant, an oxidizing agent, etc. to the dielectric layer and chemically or electrolytically polymerizing the solution in situ. Alternatively, a pre-synthesized conductive polymer may be applied to the dielectric layer. In this case, for example, a liquid polymer dispersion containing a conductive polymer and a polymer dopant may be impregnated into the dielectric layer to form a film of the conductive polymer that covers at least a part of the dielectric layer.
[0066] As the conductive polymer, polypyrrole, polythiophene, polyaniline, etc. are preferable. These may be used alone, or two or more may be used in combination, or a copolymer of two or more monomers may be used. In this specification, polypyrrole, polythiophene, polyaniline, etc. refer to polymers having polypyrrole, polythiophene, polyaniline, etc. as a basic skeleton, respectively. Therefore, polypyrrole, polythiophene, polyaniline, etc. may also include their respective derivatives. For example, polythiophene includes poly(3,4-ethylenedioxythiophene) (PEDOT), etc. The weight-average molecular weight of the conductive polymer is not particularly limited, but is, for example, 1000 to 100,000.
[0067] From the viewpoint of suppressing dedoping from the conductive polymer, it is desirable to use a polymer dopant (polymer anion, etc.). It is considered that dedoping of the polymer dopant is suppressed by the liquid component containing a first coordination compound (complex anion, etc.), and therefore deterioration of the conductive polymer or a decrease in conductivity is suppressed. Examples of the polymer dopant (polymer anion, etc.) include anions such as polyvinyl sulfonic acid, polystyrene sulfonic acid, polyallyl sulfonic acid, polyacryl sulfonic acid, polymethacryl sulfonic acid, poly(2-acrylamido-2-methylpropane sulfonic acid), polyisoprene sulfonic acid, and polyacrylic acid. These may be used alone or in combination of two or more. In addition, these may be homopolymers or copolymers of two or more monomers. Among them, polystyrene sulfonic acid (PSS) is preferable. The weight average molecular weight of the polymer dopant is not particularly limited, but is preferably, for example, 1000 to 1,000,000 in terms of easiness in forming a homogeneous solid electrolyte layer.
[0068] The present invention will be described in more detail below based on the embodiments, however, the present invention is not limited to the following embodiments.
[0069] FIG. 1 is a schematic cross-sectional view of the electrolytic capacitor according to this embodiment, and FIG. 2 is a schematic exploded view of a portion of a capacitor element of the electrolytic capacitor.
[0070] 1 includes a capacitor element 10, a bottomed case 11 that houses capacitor element 10, a sealing member 12 that closes the opening of bottomed case 11, a seat plate 13 that covers sealing member 12, lead wires 14A, 14B that extend from sealing member 12 and pass through seat plate 13, lead tabs 15A, 15B that connect the lead wires to electrodes of capacitor element 10, and a liquid component (not shown). The open end of bottomed case 11 is curled so as to be crimped to sealing member 12.
[0071] Capacitor element 10 is made from a wound body as shown in Fig. 2. The wound body is a semi-finished product of capacitor element 10, in which a conductive polymer is not disposed between anode body 21 and cathode body 22 having a dielectric layer on the surface. The wound body is obtained by winding anode body 21 connected to lead tab 15A and cathode body 22 connected to lead tab 15B with separator 23 interposed therebetween. The outermost periphery of the wound body is fixed by stop tape 24. Note that Fig. 2 shows a state in which a part of the wound body is unfolded before the outermost periphery is fixed.
[0072] The anode body 21 comprises a metal foil having a roughened surface, and a dielectric layer is formed on the roughened surface. A conductive polymer is attached to at least a portion of the surface of the dielectric layer to form the capacitor element 10. The capacitor element 10 is housed in an exterior case together with a liquid component (not shown).
[0073] An example of a method for manufacturing an electrolytic capacitor will now be described. (i) preparing an anode body 21 and a cathode body 22 having a dielectric layer; Metal foil made of a valve metal is used as the raw material for anode body 21 and cathode body 22. In the case of anode body 21, the surface of the metal foil is roughened by etching or the like to form a plurality of projections and recesses on the surface of the metal foil. Next, a dielectric layer is formed on the roughened surface of the metal foil by chemical conversion or the like. If necessary, the surface of cathode body 22 may be roughened.
[0074] (ii) Preparation of the roll Anode body 21 and cathode body 22 are wound with separator 23 interposed therebetween to produce a wound body. Separator 23 may be a nonwoven fabric containing synthetic cellulose or the like as a main component. Stop tape 24 is placed on the outer surface of cathode body 22 located in the outermost layer of the wound body to fix the end of cathode body 22. If necessary, the wound body is further subjected to a chemical conversion treatment.
[0075] (iii) Step of forming capacitor element 10 For example, a liquid polymer dispersion is impregnated into the dielectric layer to form a conductive polymer film that covers at least a portion of the dielectric layer. This results in a capacitor element 10 in which a conductive polymer is disposed between the anode body 21 and the cathode body 22. The step of applying the polymer dispersion to the surface of the dielectric layer may be repeated two or more times. Thereafter, the capacitor element 10 may be impregnated with a liquid component. This results in an electrolytic capacitor comprising a conductive polymer and a liquid component.
[0076] (iv) Sealing the capacitor element Capacitor element 10 is housed in bottomed case 11 together with the liquid component so that lead wires 14A and 14B are located on the opening side of bottomed case 11. Next, the opening of bottomed case 11 is sealed with sealing member 12 through which each lead wire passes, and the opening end is crimped to sealing member 12 and curled, and seat plate 13 is placed on the curled portion to complete the electrolytic capacitor as shown in FIG.
[0077] In the above embodiment, a wound-type electrolytic capacitor has been described, but the scope of application of the present invention is not limited to the above, and the present invention can also be applied to other electrolytic capacitors, for example, chip-type electrolytic capacitors that use a metal sintered body as an anode body, and stacked-type electrolytic capacitors that use a metal plate as an anode body.
[0078] [Example] The present invention will be described in more detail based on examples and comparative examples, but the present invention is not limited to the examples.
[0079] Preparation of liquid components The components shown in Table 1 were mixed to prepare liquid components LA1 to LA11 (Examples) and LB1 to LB4 (Comparative Examples).
[0080] [Rating 1] The liquid components LA1 to LA11 and LB1 to LB4 in Table 1 were used to measure pH changes due to heating. More specifically, 30 mL of liquid component was weighed into a glass container with a hermetic lid, and the pH (X) of the liquid component in the container at 25°C was measured using HM-41X manufactured by DKK-TOA. Next, the container containing the liquid component was sealed and kept in an oven at 145°C for 1000 hours, after which the temperature of the liquid component in the container was returned to 25°C and the pH (Y) was measured again. The difference between the measured values Y and X was calculated to evaluate the change in pH. The results are shown in Table 2.
[0081] TIFF0007624609000003.tif116170
[0082] [Table 2]
[0083] <<Preparation of electrolytic capacitors CA1 to CA6 and CB1 to CB6>> A wound electrolytic capacitor (diameter 8.0 mm×L (length) 12.0 mm) with a rated voltage of 100 V and a rated capacitance of 15 μF was fabricated. A specific method for fabricating the electrolytic capacitor will be described below.
[0084] (Preparation of anode body) An aluminum foil having a thickness of 100 μm was etched to roughen the surface of the aluminum foil. Then, a dielectric layer was formed on the surface of the aluminum foil by chemical conversion treatment. The chemical conversion treatment was performed by immersing the aluminum foil in an ammonium adipate solution and applying a voltage of 180 V to the aluminum foil. The aluminum foil was then cut to prepare an anode body.
[0085] (Preparation of the cathode body) An aluminum foil having a thickness of 50 μm was subjected to an etching treatment to roughen the surface of the aluminum foil, and then the aluminum foil was cut to prepare a cathode body.
[0086] (Making of the roll) An anode lead tab and a cathode lead tab were connected to the anode body and the cathode body, and the anode body and the cathode body were wound with the lead tabs interposed between them. An anode lead wire and a cathode lead wire were connected to the ends of the lead tabs protruding from the wound body, respectively. The wound body thus produced was subjected to a chemical conversion treatment again, and a dielectric layer was formed on the cut ends of the anode body. Next, the ends of the outer surface of the wound body were fixed with a winding stop tape to produce the wound body.
[0087] (Preparation of polymer dispersion) 3,4-ethylenedioxythiophene and the polymer dopant polystyrene sulfonic acid (PSS, weight-average molecular weight 100,000) were dissolved in ion-exchanged water to prepare a mixed solution. Iron (III) sulfate (oxidant) dissolved in ion-exchanged water was added while stirring the mixed solution to carry out a polymerization reaction. After the reaction, the resulting reaction solution was dialyzed to remove unreacted monomers and excess oxidant, and a polymer dispersion containing polyethylenedioxythiophene doped with approximately 5% by mass of PSS (PEDOT / PSS) was obtained.
[0088] (Formation of solid electrolyte layer) The wound body was immersed in a polymer dispersion contained in a specified container in a reduced pressure atmosphere (40 kPa) for 5 minutes, and then pulled out of the polymer dispersion. The wound body impregnated with the polymer dispersion was then dried in a drying oven at 150°C for 20 minutes to form a solid electrolyte layer made of a conductive polymer layer covering at least a part of the dielectric layer.
[0089] (Preparation of liquid components) The components shown in Table 3 were mixed to prepare liquid components LA1, LA2, LA12 to LA15 (Examples) and LB1 to LB4 (Comparative Examples).
[0090] (Assembling electrolytic capacitors) The above-mentioned wound body with the solid electrolyte formed thereon was immersed for 5 minutes in a reduced pressure atmosphere (40 kPa) in the liquid components shown in Table 3. This resulted in a capacitor element impregnated with the liquid components. The resulting capacitor element was sealed to complete an electrolytic capacitor as shown in Figure 1. After that, an aging treatment was performed at 130°C for 2 hours while applying the rated voltage.
[0091] [Rating 2] (Capacitance and ESR measurements) The electrostatic capacitance and initial ESR of the obtained electrolytic capacitor were measured. In order to evaluate the long-term reliability, the capacitor was held at 145°C for 2000 hours while applying the rated voltage, and the increase rate of ESR (ΔESR) was confirmed. ΔESR is expressed as the ratio (Z / Z0) of ESR (Z) after holding at 145°C to the initial value (Z0). The evaluation results are shown in Table 4. Table 4 also shows the change in pH (YX) for each liquid component, which was determined in the same manner as in Evaluation 1.
[0092] TIFF0007624609000005.tif92170
[0093] [Table 4]
[0094] Electrolytic capacitors CA7 to CA10 and CB5 to CB8 Except for not carrying out the preparation of the polymer dispersion and the formation of the solid electrolyte, electrolytic capacitors were produced in the same manner as the electrolytic capacitors CA1 to CA4 and CB1 to CB4, and then aging treatment was carried out. Evaluation 2 was carried out using the obtained electrolytic capacitors. The evaluation results are shown in Table 5. Table 5 also shows the change in pH (YX) of each liquid component.
[0095] [Table 5]
[0096] Although the present invention has been described with respect to the presently preferred embodiments, such disclosure should not be interpreted as limiting. Various variations and modifications will no doubt become apparent to those skilled in the art to which the present invention pertains upon reading the above disclosure. Accordingly, the appended claims should be interpreted to cover all variations and modifications without departing from the true spirit and scope of the present invention. [Industrial Applicability]
[0097] The liquid component of the present disclosure is useful in aluminum electrolytic capacitors and electrolytic capacitors having a conductive polymer and a liquid component. [Explanation of symbols]
[0098] 10: capacitor element, 11: bottomed case, 12: sealing member, 13: seat plate, 14A, 14B: lead wires, 15A, 15B: lead tabs, 21: anode body, 22: cathode body, 23: separator, 24: winding stop tape
Claims
1. a central atom being boron; a ligand having a plurality of coordinating atoms bonded to the central atom; and at least one first cation selected from the group consisting of a cation containing a nitrogen atom and a cation containing a phosphorus atom; the coordinating atom is at least one selected from the group consisting of oxygen and nitrogen, and is bonded to a carbon atom that does not have an oxo group; the central atom and the ligand form a complex anion, a ratio of the complex anion in an electrolyte salt containing the complex anion and the first cation is 15 mass % or more and 90 mass % or less.
2. 2. The liquid component for an electrolytic capacitor according to claim 1, which exhibits an increase in pH of 3 or less when held at a temperature of 145° C. for 1000 hours.
3. 2. The liquid component for an electrolytic capacitor according to claim 1, wherein a molar ratio of said complex anion to said first cation (=complex anion / first cation) is 0.9 or more and 1.1 or less.
4. The liquid component for an electrolytic capacitor according to any one of claims 1 to 3, wherein the first cation includes at least one selected from the group consisting of a secondary ammonium ion, a tertiary ammonium ion, and a quaternary ammonium ion.
5. The liquid component for an electrolytic capacitor according to any one of claims 1 to 4, wherein the first cation includes a quaternary ammonium ion.
6. 6. The liquid component for an electrolytic capacitor according to claim 1, wherein the content of the complex anion is 0.1% by mass or more and 30% by mass or less.
7. 7. The liquid component for an electrolytic capacitor according to claim 1, wherein the amount of water contained in the liquid component is 0.1 to 30 mass % or less.
8. the ligand is derived from a polyol having an aromatic ring and at least a primary hydroxyl group and a secondary hydroxyl group; the primary hydroxy group is attached to the aromatic ring; the group containing the second hydroxy group is attached in an ortho position relative to the first hydroxy group; 8. The liquid component for an electrolytic capacitor according to claim 1, wherein the group containing the second hydroxyl group is the second hydroxyl group or an alkyl group having 1 to 4 carbon atoms and having the second hydroxyl group.
9. 9. The liquid component for an electrolytic capacitor according to claim 8, wherein two or three of the ligands are coordinated to one of the central atoms.
10. The liquid component for an electrolytic capacitor according to any one of claims 1 to 9, further comprising a polymeric polyether solvent.
11. The liquid component for an electrolytic capacitor according to any one of claims 1 to 10, wherein the ligand contains a substituent having electron-withdrawing properties.
12. an anode body having a dielectric layer formed on a surface thereof; A cathode body; An electrolytic capacitor comprising: a conductive polymer disposed between the anode body and the cathode body; and the liquid component according to any one of claims 1 to 11.
13. The electrolytic capacitor according to claim 12 , wherein the conductive polymer is doped with a dopant.
14. The electrolytic capacitor of claim 13 , wherein the dopant comprises a polymeric anion.
15. an anode body having a dielectric layer formed on a surface thereof; A cathode body; and the liquid component according to any one of claims 1 to 11 disposed between the anode body and the cathode body.
16. The electrolytic capacitor according to any one of claims 12 to 15, wherein the liquid component has a pH of 6 or less.
Citation Information
Patent Citations
Driving electrolyte for electrolytic capacitor
JP1987213238A
Driving electrolyte for electrolytic capacitor
JP1987213239A
Electrolyte for driving electrolytic capacitor
JP1989114018A
Electrolyte for driving electrolytic capacitor
JP1991091225A
Electrolyte for driving electrolytic capacitor and electrolytic capacitor using same
JP1991129717A